Impact of Donor Age on the Osteogenic Supportive Capacity of Mesenchymal Stromal Cell-Derived Extracellular Matrix - Carvalho, Marta S.; Alves, Laura; Bogalho, Isabel; Cabral, Joaquim M. S.; da Silva, Cláudia L. (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSC) have been proposed as an emerging cell-based therapeutic option for regenerative medicine applications as these cells can promote tissue and organ repair. In particular, MSC have been applied for the treatment of bone fractures. However, the healing capacity of these fractures is often compromised by patient’s age. Therefore, considering the use of autologous MSC, we evaluated the impact of donor age on the osteogenic potential of bone marrow (BM)-derived MSC. MSC from older patients (60, 80 years old) demonstrated impaired proliferative and osteogenic capacities compared to MSC isolated from younger patients (30, 45 years old), suggesting that aging potentially changes the quantity and quality of MSC. Moreover, in this study, we investigated the capacity of the microenvironment (i.e. extracellular matrix (ECM)) to rescue the impaired proliferative and osteogenic potential of aged MSC. In this context, we aimed to understand if BM MSC features could be modulated by exposure to an ECM derived from cells obtained from young or old donors. When aged MSC were cultured on decellularized ECM derived from young MSC, their in vitro proliferative and osteogenic capacities were enhanced, which did not happen when cultured on an old ECM. Our results suggest that the microenvironment, specifically the ECM, plays a crucial role in the quality (assessed in terms of osteogenic differentiation capacity) and quantity of MSC. Specifically, the aging of ECM is determinant for osteogenic differentiation of MSC. In fact, old MSC maintained on a young ECM produced higher amounts of extracellularly deposited calcium (9.10±0.22 vs 4.69±1.41 µg.µL-1.10-7 cells for young ECM and old ECM, respectively) and upregulated the expression of osteogenic gene markers, such as Runx2 and OPN. Cell rejuvenation by exposure to a functional ECM might be a valuable clinical strategy to overcome the age-related decline in the osteogenic potential of MSC by recapitulating a younger microenvironment, attenuating the effects of aging on the stem cell niche. Overall, this study provides new insights on the osteogenic potential of MSC during aging and opens new possibilities for developing clinical strategies for elderly patients with limited bone formation capacity who currently lack effective treatments.